Advancing Renewable Energy Operations with Satellite Technology - Patro, Ravindra Kumar; Choudhury, Shaswati Roy; Choudhury, Shayan Roy; Chandra, Subhash (International Journal of Supply Chain and Logistics, 2024)
Purpose: This research examines how businesses in the renewable energy sector can leverage technology, particularly satellite technology, to navigate geopolitical complexities and achieve sustainable growth. Methodology: The study employs a multidisciplinary approach, combining historical analysis, case studies, and quantitative data analysis to uncover key trends and strategic implications. Findings: The research reveals that drone technology offers significant potential for enhancing last-mile delivery efficiency, particularly in urban areas and remote locations, aligning with findings from studies like those by Murray & Chu (2015). However, the study identifies considerable obstacles, including regulatory challenges, limited payload capacities, and public acceptance issues. Solutions such as airspace regulation frameworks, collaborative logistics networks, and advanced battery technologies are highlighted as critical enablers for successful drone integration. Contribution to Theory, Policy and Practice: This research underscores the importance of understanding the complex relationship between technology and geoeconomics for informed decision-making in the renewable energy sector. It also highlights the potential of satellite technology for optimizing operations and managing risks, paving the way for further exploration and innovation in this field.